Assessment of construction planning of new project : Medan Ikan Bakar case study - Siti Farahanum, Ab Rahim (2018)
A construction project is commonly acknowledged as successful when it is completed on time, within budget, in accordance with specifications and to stakeholder satisfaction. During the project execution, delay in the project is one of the failures that usually occurred in the construction industry, which leads to extension of time where the project cannot be completed according to the plan. The objective of this study was focused on assessment of construction planning of new project Medan Ikan Bakar. The existing plan of the Medan Ikan Bakar project is analysed and it has been identified that the delay was occurred during the project execution. Due to the extension of time that occurred in the project, the reschedule plan of the Medan Ikan Bakar project is carried out by considering the number of rainy days and the public holidays. Hence, the optimum working days is obtained and the project could be completed according to the plan so that the users may not face the lost in the term of the operation of the building where the completed project is beyond the expected date. After acquiring the optimum working days in construction planning, several suggestions could be created for the development of strategies with the purpose in improving construction planning practices and can be as a guideline for future study in planning the construction project.